Fuzzy C-Mean untuk Mengcluster Pemain Football FIFA (Studi Kasus: Data Kaggle) - Mohammad Afan; Retno Wardhani; Nur Nafi’iyah (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2019)
From the data set in the internet world, we want to do the management. The purpose of managing existing data on the internet especially Kaggle is to find out how the clustering process is and how to apply the c-mean fuzzy algorithm. Fuzzy c-mean is used to cluster and get the centroid value of each cluster. The results of the centroid value of each cluster are used to group new data or the dataset itself. We use the FIFA Football Kaggle dataset to cluster into 2 and 3 groups. Fuzzy c-mean algorithm is implemented to cluster data with 2499 rows with 46 variables. The tool used to process data is matlab. Keywords— FIFA Fottbal, Clustering, Fuzzy C-mean, Matlab